Swelling‐Mediated Mechanical Stimulation Regulates Differentiation of Adipose‐Derived Mesenchymal Stem Cells for Intervertebral Disc Repair Using Injectable UCST Microgels. Issue 3 (31st October 2022) - Huang, Xianpeng; Chen, Di; Liang, Chengzhen; Shi, Kesi; Zhou, Xiaopeng; Zhang, Yuang; Li, Yi; Chen, Jiangjie; Xia, Kaishun; Shu, Jiawei; Yang, Biao; Wang, Jingkai; et al.
Abstract: Mechanical stimulation is an effective approach for controlling stem cell differentiation in tissue engineering. However, its realization in in vivo tissue repair remains challenging since this type of stimulation can hardly be applied to injectable seeding systems. Here, it is presented that swelling of injectable microgels can be transformed to in situ mechanical stimulation via stretching the cells adhered on their surface. Poly(acrylamide‐ co ‐acrylic acid) microgels with the upper critical solution temperature property are fabricated using inverse emulsion polymerization and further coated with polydopamine to increase cell adhesion. Adipose‐derived mesenchymal stem cells (ADSCs) adhered on the microgels can be omnidirectionally stretched along with the responsive swelling of the microgels, which upregulate TRPV4 and Piezo1 channel proteins and enhance nucleus pulposus (NP)‐like differentiation of ADSCs. In vivo experiments reveal that the disc height and extracellular matrix content of NP are promoted after the implantation with the microgels. The findings indicate that swelling‐induced mechanical stimulation has great potential for regulating stem cell differentiation during intervertebral disc repair. Abstract : The preparation and implantation of microgels with upper critical solution temperature (UCST) properties for intervertebral disc repair are presented. The UCST microgel exhibits satisfactory biocompatibility. The swelling‐mediated mechanical stimulation enhances nucleus pulposus‐like differentiation of adipose‐derived mesenchymal stem cells (ADSCs). Also, transplantation of UCST microgels with ADSCs significantly ameliorates the degenerative disc disease model in rats.